Spirituality-Based Intervention in Hypertension: EFfects on Blood PrEssure and EndotheliaL Function—FEEL Trial Results - Maria Emília Figueiredo Teixeira; Weimar Kunz Sebba Barroso; Andréa Araújo Brandão; Ana Luiza Lima Sousa; Roberto Esporcatte; Mário Henrique Elesbão de Borba; Ana Clara Neri Ávila Baleeiro; Beatriz Caldas Gonçalves; Enzo Inumaru; Enzo Mata de Sousa; Giovana Barros Leal; Henrique Soares de Araújo Pereira Farias; et al. (Global Heart)
Background: Emerging evidence suggests that spirituality improves patient outcomes, however, this has undergone only limited evaluation in randomized trials. Hypertension is a major cause of cardiovascular morbidity and mortality worldwide. Objectives: To evaluate whether a spirituality-based intervention, compared to a control group, can reduce blood pressure (BP) and improve endothelial function after 12 weeks in patients with mild or moderate hypertension (HTN). Methods: Open randomized controlled trial of adults with stage I or II hypertension. Following baseline evaluation, including lifestyle questionnaires, and measurements of office and central blood pressure (BP), home blood pressure monitoring (HBPM) and flow mediated dilation (FMD), patients were randomized to a spirituality-based intervention, which included training for forgiveness, gratitude, optimism, and life purpose delivered by daily WhatsApp communications, or to the control group (CG). Main outcomes were between group difference in change from baseline to 12 weeks in office and central BP, HBPM and FMD, using t-tests, analyses of covariance (ANCOVA) adjusting for baseline differences, and, in addition, missing data imputation as a sensitivity analysis. Results: Fifty-one patients were randomized to spirituality-based intervention and 49 to control group. Baseline characteristics were well balanced between groups. Spirituality training, compared with control, improved 7.6 mmHg office systolic blood pressure (SBP), 4.1 mmHg central SBP and 4.1 percentage points FMD. Compared to control group, t-test demonstrated statistical significance for office SBP (–7.04 mmHg, p = 0.047) and FMD (7.46 percentage points, p < 0.001), and ANCOVA adjustment for baseline differences showed statistical significance for central SBP (–6.99 mmHg, p = 0.038) and FFMD (7.95 percentage points, p < 0.001) There was no significant effect on HBPM. Conclusion: A spirituality-based intervention was associated with improved control of office SBP and FMD. These findings will be prospectively evaluated in a nationwide larger and well-powered RCT.